EDUKASI PEMENUHAN GIZI PADA IBU HAMIL DI DESA BARUAS KOTA PADANGSIDIMPUIAN: EDUKASI PEMENUHAN GIZI PADA IBU HAMIL DI DESA BARUAS KOTA PADANGSIDIMPUIAN - Ahmad, Haslinah; mutia, Fatma; harahap, yana wari (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2024)
Pregnancy is a time when nutritional needs become higher, and meeting these needs has a positive effect on the health of the mother and the unborn baby. Nutrition deserves special attention during pregnancy and breastfeeding because of the high nutritional needs and the important role of nutrition for the fetus and baby. This community service aims to make the community more aware of the importance of nutrition for pregnant women. The method used in this community service is to increase public knowledge about the meaning of nutrition, nutritional needs and nutritional goals for pregnant women. The number of participants in this activity is 30 people. This activity is carried out in coordination with village officials and their staff which is continued with free examinations and treatment where there is health education with counseling and health examination activities such as measuring blood pressure, checking lila, checking cholesterol and weighing weight carried out by health workers and finally education related to providing nutrition for pregnant women. Conclusion Counseling activities can be carried out more often so that pregnant women provide more nutrition for pregnant women. And counseling activities provide nutrition for pregnant women according to health requirements and can increase knowledge in terms of health.